Anthropometric Indicators for Blood Pressure and the Prevalence of Hypertension in Indonesian College Students Aged 18-25 Years - Hastuti, Janatin; Rahmawati, Neni Trilusiana; Suriyanto, Rusyad Adi (Pakistan Journal of Nutrition, 2018)
Background and Objective: Anthropometric measures have been reported to be associated with elevated blood pressure. Understanding these factors may prevent the increasing level of hypertension. This study aimed to examine some anthropometric indicators for blood pressure and the prevalence of hypertension in Indonesian college students (18-25 years) in Yogyakarta. Materials and Methods: A total of 209 male and 258 female students (18-25 years) in Yogyakarta participated in this study. Weight, stature, circumferences at mid upper arm (MUAC), wrist, waist, hips, total of four skinfolds and systolic and diastolic blood pressure were measured. Body mass index (BMI), body frame index, waist-to-hip ratio (WHR) and waist-to-stature ratio (WSR) were determined. Analyses of t-test, chi-square test and simple and multiple linear regression analyses were conducted. Results: The prevalence of hypertension was low (14.0% in boys, 1.6% in girls), but that of prehypertension was high (43.0% in boys, 18.1% in girls). All anthropometric measures (weight, MUAC, wrist circumference, WC, HC, skinfold thickness, BMI and WSR) except for stature and WHR were significantly associated with systole and diastole in boys and systole in girls (r= 0.13 - 0.32, p<0.05, p<0.01, respectively). The BMI and MUAC were the strongest predictors of systole in boys and girls, respectively. Diastole was predicted better by weight and MUAC together and weight alone in boys and weight in girls. Conclusion: The prevalence of hypertension was higher in boys than in girls. All anthropometric measures except stature and WHR were significantly associated with systole and diastole in boys and systole in girls. The BMI in boys and MUAC in girls were the strongest contributors in systole, whereas, weight and MUAC in boys and weight in girls were the strongest predictors of diastole.